Stimulation of glucose uptake by edible Pholiota nameko (T.Itô) S.Ito & S.Imai extract counteracts palmitate-induced insulin resistance in C2C12 myotubes - Vong, Seng-Kai; Chen, Chiao-Ming; Das, Arpita; Shyur, Lie-Fen; Ju, Yu-Ming; Hsieh, Huei-Mei; Yang, Shu-Hui; Varga, Viola; Li, Sing-Chung (Frontiers in Sustainable Food Systems, 2025)
Pholiota nameko (P. nameko) was identified as an edible mushroom known for its abundance of bioactive compounds. Previous studies suggested that extracts from this mushroom possess antioxidant properties attributed to the presence of phenolic acids, such as 4-hydroxybenzoic acid (4-HBA) and cinnamic acid (CA). These compounds show promise in potentially ameliorating insulin resistance. In this study, the highest levels of 4-HBA and CA were selected from six P. nameko extracts using ultra-high-pressure liquid chromatography (UHPLC) to investigate whether they could improve the glucose uptake resistance induced by palmitate in C2C12 myotubes. Additionally, the protein expression of GLUT4 was examined. The results indicated that P. nameko hot water extract (PN-HW) exhibited the highest total polyphenol content (9.34 ± 0.31 mg GAE/g) and demonstrates strong free radical scavenging ability (77.4 ± 1.1%). Furthermore, PN-HW contains notable amounts of 4-HBA (4.02 ± 0.17 mg/g DW) and CA (2.01 ± 0.09 mg/g DW). Importantly, the cell viability reveals that PN-HW extracts did not have a toxic effect on C2C12 myotubes. PN-HW significantly enhances glucose uptake at doses of 25 μg/mL. Hence, it was suggested that PN-HW might contain elevated levels of phenolic acids, potentially mitigating impaired glucose uptake caused by high-fat content and consequently enhancing the glucose uptake capacity of C2C12 cells.